Antibiotic Prescription Practices among Dentists After Extractions in Lahore: Antibiotic Prescription Practices among Dentists - Amin, Salman; Anwar, Malik Adeel; Sammar, Rehma; Saeed, Tooba; Rehman, Ijaz Ur; Abid, Anum; Baig, Moghees A (Pakistan Journal of Health Sciences, 2025)
Antibiotics, discovered by Sir Alexander Fleming in 1929, have significantly advanced medical therapeutics. However, the rising antibiotic resistance has been the result of its overuse in the past few decades. Objective: To evaluate the antibiotic prescribing practices after dental extractions of house officers in Lahore. Methods: A study was conducted with a sample size of 127 house officers/interns from March to June 2024, from various dental hospitals in Lahore. These participants were asked to complete an anonymous questionnaire that explored their knowledge, attitudes, and practices related to prescribing antibiotics following tooth extractions. The data collected were analyzed using SPSS version 25.0 to identify trends and gaps in their understanding. Results: The participants had an average age of 23.77 years, with slightly more females than males. A vast majority (92.1%) prescribed antibiotics when a patient had a periapical abscess with a fever, while fewer (18.9%) did so simply because a patient requested it after a routine extraction. A significant knowledge gap among house officers in classifying antibiotics, with 81.1% incorrectly identifying Azithromycin as a broad-spectrum antibiotic and 64.6% misclassifying narrow-spectrum antibiotics. Conclusions: This study highlighted that while there is a general awareness of antibiotic resistance among house officers, there is still a significant gap in their adherence to proper guidelines when prescribing antibiotics after tooth extractions. The findings suggested a need for multi-prog strategies and their application to ensure that antibiotics are used judiciously, thereby helping to combat the growing problem of antibiotic resistance.